Teachers' Beliefs About Assessment in an EFL Context in Colombia - Ana Patricia Muñoz; Marcela Palacio; Liliana Escobar (Universidad Nacional de Colombia, 2012)
There is evidence that teachers' beliefs on teaching and learning exert an influence on the way they teach and assess learning, and on what students learn. Therefore, it is central that overt attention is devoted to the perceptions teachers have and how they influence teaching and learning. In this article we describe a study on teachers' beliefs about assessment, in general, and about the assessment systems used at a language center of a private university in Colombia. Surveys, written reports, and interviews were used to research the beliefs of sixty-two teachers. Results indicate a contradiction between what they say they do and what they believe, suggesting that teachers need opportunities for reflection, selfassessment and more guidance on formative assessment practices.